2017
DOI: 10.1111/exd.13390
|View full text |Cite
|
Sign up to set email alerts
|

3D In vitro model of the re‐epithelialization phase in the wound‐healing process

Abstract: Keratinocytes of the basal layer function are to maintain tissue homoeostasis and to fulfil skin repair in response to an external aggression. In wound-healing, during re-epithelialization phase, epithelial precursor cells gradually migrate from the edges of the wound. The epidermal reconstruction model called standard model allows the vertical skin regeneration process (proliferation/differentiation) to being investigated, and keratinocyte function in preserving skin homoeostasis to being assessed. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Keratinocytes in the basal layer of the skin play a major role in the maintenance of tissue homoeostasis and in skin repair in response to a cutaneous injury ( Deshayes et al, 2018 ). During the re-epithelialization process, epithelial precursor cells migrate from the edges of the wound, proliferate and differentiate to create a new epidermis ( Deshayes et al, 2018 ). Previous studies have demonstrated that keratinocyte function is essential in wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…Keratinocytes in the basal layer of the skin play a major role in the maintenance of tissue homoeostasis and in skin repair in response to a cutaneous injury ( Deshayes et al, 2018 ). During the re-epithelialization process, epithelial precursor cells migrate from the edges of the wound, proliferate and differentiate to create a new epidermis ( Deshayes et al, 2018 ). Previous studies have demonstrated that keratinocyte function is essential in wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…Original studies employing alternative methods have been frequently published in Experimental Dermatology in the last years . In line with this tradition, the present special issue also showcases a number of original contributions, which can be viewed as current examples for new developments in alternative methods. The advances in reproducing human skin features in vitro make it possible to recapitulate also human skin diseases, thus replacing the use of animals and/or reducing their number by integrating in vivo and in vitro data.…”
mentioning
confidence: 54%
“…The process of epidermal regeneration is a multi-step process that is regulated by a range of cytokine and cell types, ultimately leading to the reconstruction of the damaged skin barrier. 21 Exosomes derived from mesenchymal stem cells have been repeatedly shown to accelerate re-epithelialization and to thereby enhance wound healing. 22,23 Our present results indicated that PRP-Exo treatment similarly promoted enhanced epithelialization, highlighting the promise of these particles for use in the treatment of chronic wounds.…”
Section: Discussionmentioning
confidence: 99%